The Influence of Advertising Attractiveness and Online Customer Reviews on Trust – Mediated Purchase Decision on Consumers of Hotel Services in the Tiket.com Application - Rahayu, Dwi; Sutiono, Heru Tri; Wisnalmawati, Wisnalmawati (Westscience Press, 2024)
The purpose of this research is to determine the influence of Advertising Attractiveness and Online Customer Reviews on Purchase Decisions through Trust. The sample for this research consisted of 95 people who had not used or had ever used hotel services on the Tiket.com Application. This research uses a quantitative descriptive approach. The collected data is then processed using SmartPLS 3.0 software. The findings of this research show that Advertising Attractiveness has a positive and significant effect on Purchase Decisions, Online Customer Reviews has a positive and insignificant effect on Purchase Decisions, then Trust mediates the influence of Advertising Attractiveness and Online Customer Reviews on Purchase Decisions and Trust has a positive and significant effect on Purchase Decisions.